The Study of Arabic Conversation Skills was carried out at elementary school - Joana, Charvet; Yuri, Jennifer; Crosbie, Kho (Lingeduca: Journal of Language and Education Studies, 2023)
This study aims to train students' Arabic conversation skills at the elementary school level. The conversation skills of students at the elementary school level are very low, so students at the elementary level are awkward to communicate using Arabic. With Arabic-based conversational learning aimed at encouraging, guiding, developing and fostering abilities and cultivating a positive attitude towards Arabic conversation skills, both receptively and productively, students at the elementary school level can learn Arabic conversation skills. So that these students can communicate using Arabic conversation through the study. The method used by the researcher in conducting this research was a survey method and in-depth interviews, in which at this stage the researcher conducted interviews with elementary level students by asking questions to these students, so that with these answers the researcher could collect data from students at the elementary level. the basis. The researcher hopes that with this research on Arabic conversation skills study, students can add knowledge and insight about the Arabic conversation skills. Therefore, in order to increase the insight and knowledge of elementary level students about the study of conversational Arabic skills, researchers can conduct research related to the study of conversational skills of Arabic students at the elementary school level.